2019
DOI: 10.1108/ejim-08-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social capital on exploratory and exploitative innovation

Abstract: Purpose The purpose of this paper is to advance new insights into how internal and external social capital (SC) facets influence exploratory and exploitative innovation directly, and indirectly through absorptive capability (AC), by drawing on the relational and knowledge-based views. Design/methodology/approach The paper empirically tests the developed model using 135 survey responses from managers in construction contractor firms. Data were factor analysed, and path estimates determined using partial least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 114 publications
(273 reference statements)
6
34
0
Order By: Relevance
“…Recent studies have shown, from a qualitative point of view, how internal SC positively impacts performance in knowledge-intensive contexts ( Salas−Vallina et al, 2020 ). Other papers have analyzed the relationships between SC and PACP (knowledge identification capability and external knowledge acquisition) ( Ortiz et al, 2017 , 2018 ), and others have focused on examining the mediating role of absorptive capacity (PACAP and RACAP) on the relationship of SC and innovation ( Duodu and Rowlinson, 2019 ; Wang et al, 2020 ). However, most of them have focused on analyzing SC from an external or inter-organizational point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown, from a qualitative point of view, how internal SC positively impacts performance in knowledge-intensive contexts ( Salas−Vallina et al, 2020 ). Other papers have analyzed the relationships between SC and PACP (knowledge identification capability and external knowledge acquisition) ( Ortiz et al, 2017 , 2018 ), and others have focused on examining the mediating role of absorptive capacity (PACAP and RACAP) on the relationship of SC and innovation ( Duodu and Rowlinson, 2019 ; Wang et al, 2020 ). However, most of them have focused on analyzing SC from an external or inter-organizational point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to adopt a quantitative technique to study the investigated topic and assess the survey data using an ordinary least squares (OLS) regression analysis appears to be appropriate and justified because previous studies have called for a more finegrained understanding of the contribution SIC could offer to firm innovativeness (McElroy, 2002). The choice to adopt a quantitative method was in line with the proposed research and with previous studies (Duodu and Rowlinson, 2019). It was based on the analysis of the relationship between sharing resources and sharing intensity (independent variables) and their effect on SIC (dependent variable).The OLS regression results are presented in Table 4.…”
Section: Analysis and Resultsmentioning
confidence: 80%
“…Observed as the technology advancement receptivity, Zahra and George (2002) formulate it as the organisation's capability to acquire, absorb, transform and apply knowledge. Absorptive aptitude is also deemed as the firm's ability to learn from others (Duodu & Rowlinson, 2019). Hence, it is perceived as the firm's internal process, which shows how they can prior knowledge such as experience and existing practices (Easterby-Smith et al, 2008).…”
Section: The Underpinning Driversmentioning
confidence: 99%